Achieving a firm's competitive advantage through dynamic capability. Issue 3 (4th July 2016) - Lin, Chinho; Tsai, Hua-Ling
Abstract : Purpose: – The purpose of this paper is to propose a quantitative model to help managers diagnose what dynamic capabilities a firm needs to address the demands of a rapidly changing environment. Design/methodology/approach: – A two-firm model based on the VRIO framework is built using quantitative techniques to assist top management in formulating and implementing strategies regarding when and how to develop a firm's dynamic capabilities for achieving a competitive advantage. This model is developed by considering both internal and external competences, with the former measured by the features of the organizational capabilities of the focal firm and latter evaluated by comparing the relative utilities of the dynamic capabilities of the two competing firms. Findings: – Three resource allocation strategies are introduced to guide a firm to leverage dynamic capability that generates strong organizational performance. The first two strategies are, respectively, synergy oriented, focussing on acquiring various knowledge or experiences of a capability, and uniqueness oriented, emphasizing the depth of knowledge and technology of the capabilities. The third one is a hybrid of the first two strategies. Originality/value: – The proposed model is useful to help top management determine how and when to renew, bundle, and leverage resources and capabilities in a dynamic environment. It enables decision makers to detect changes in the competitive environment and take corrective action in a timely and appropriate manner.